Link-Disjoint Broadcasting Algorithm in Wormhole-Routed 3D Petersen-Torus Networks - Jung-hyun Seo; HyeongOk Lee (International Journal of Distributed Sensor Networks)
In a network, one-to-all broadcasting is the process of disseminating messages from a source node to all the nodes existing in the network through successive data transmissions between pairs of nodes. Broadcasting is the most primary communication process in a network. A 3D Petersen-Torus (3D PT) network has been proposed recently. the three-dimensionally magnified Petersen-Torus topology, 3D PT, is suitable for establishing a wireless sensor network (WSN) in 3D rectangular or cylindrical structures such as buildings. We propose a link-disjoint broadcasting algorithm for half-duplex 3D PT networks with wormhole routing and prove that the broadcasting algorithm is link-disjoint and the broadcasting step is l / 2 + log 2 ( n - 1 ) + 5 in 3D PT ( l, n, n ) .